BioPerine Encapsulated Nanoformulation for Overcoming Drug-Resistant Breast Cancers - Sindhu C Pillai; Ankita Borah; Amandeep Jindal; Eden Mariam Jacob; Yohei Yamamoto; D. Sakthi Kumar (Elsevier, 2020)
The evolving dynamics of drug resistance due to tumor heterogeneity often creates impediments to traditional therapies making it a challenging issue for cancer cure. Breast cancer often faces challenges of current therapeutic interventions owing to its multiple complexities and high drug resistivity， for example against drugs like trastuzumab and tamoxifen. Drug resistance in the majority of breast cancer is often aided by the overtly expressed P-glycoprotein (P-gp) that guides in the rapid drug efflux of chemotherapy drugs. Despite continuous endeavors and ground-breaking achievements in the pursuit of finding better cancer therapeutic avenues, drug resistance is still a menace to hold back. Among newer therapeutic approaches, the application of phytonutrients such as alkaloids to suppress P-gp activity in drug-resistant cancers has found an exciting niche in the arena of alternative cancer therapies. In this work, we would like to present a black pepper alkaloid derivative known as BioPerine-loaded chitosan (CS)-polyethylene glycol (PEG) coated polylactic acid (PLA) hybrid polymeric nanoparticle to improve the bioavailability of BioPerine and its therapeutic efficacy in suppressing P-gp expression in MDA-MB 453 breast cancer cell line. Our findings revealed that the CS-PEG-BioPerine-PLA nanoparticles demonstrated a smooth spherical morphology with an average size of 316 nm, with improved aqueous solubility, and provided sustained BioPerine release. The nanoparticles also enhanced in vitro cytotoxicity and downregulation of P-gp expression in MDA-MB 453 cells compared to the commercial inhibitor verapamil hydrochloride, thus promising a piece of exciting evidence for the development of BioPerine based nano-drug delivery system in combination with traditional therapies as a crucial approach to tackling multi-drug resistance in cancers.